Consideraciones legales sobre datos personales en fusiones y adquisiciones - Frene, Lisandro; Aberg Cobo, Juan (Pontificia Universidad Católica del Perú, 2024)
In the last fifteen years, new technologies –’fueled’ by massive data processing– have grown at such a vertiginous pace that they have encompassed virtually all society, industries and business activities. This unprecedented technological expansion –of which data is its fuel– generated specific legislation on the processing of personal data. Thus, nowadays, in mergers and acquisitions (M&A) transactions, the legal analysis of data privacy issues of the target company is commonplace and even essential in any due diligence and minimally serious operation. In this article we will try to outline the main unavoidable legal considerations on personal data to be considered in merger and/or acquisition operations, in the respective pre and post-closing stages of such transactions.

En los últimos quince años, las nuevas tecnologías –‘alimentadas’ en base al procesamiento masivo de datos –crecieron a un ritmo tan vertiginoso que abarcaron prácticamente toda la sociedad, las industrias y actividades mercantiles. Esta expansión tecnológica sin precedentes –de la cual los datos son su combustible– generó legislación específica sobre tratamiento de datos personales. Así es que, actualmente, en las transacciones de fusiones y adquisiciones (M&A) el análisis jurídico de cuestiones de data privacy de la empresa target resulta algo corriente y hasta imprescindible en cualquier due diligence y operación mínimamente seria. En este artículo procuraremos reseñar las principales consideraciones jurídicas insoslayables sobre datos personales a tener en cuenta en las operaciones de fusión y/o adquisición, en las respectivas etapas pre y post-closing de dichas transacciones.
Legal considerations on personal data in mergers and acquisitions
Keywords: Personal data; Transaction; Due diligence; Contingencies; Contracts; Datos personales; Transacción; Due diligence; Contingencias obligaciones; https://purl.org/pe-repo/ocde/ford#5.05.00